2016
DOI: 10.1161/jaha.115.003048
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers to Improve the Prediction of Cardiovascular Event Risk in Type 2 Diabetes Mellitus

Abstract: BackgroundWe evaluated the ability of 23 novel biomarkers representing several pathophysiological pathways to improve the prediction of cardiovascular event (CVE) risk in patients with type 2 diabetes mellitus beyond traditional risk factors.Methods and ResultsWe used data from 1002 patients with type 2 diabetes mellitus from the Second Manifestations of ARTertial disease (SMART) study and 288 patients from the European Prospective Investigation into Cancer and Nutrition‐NL (EPIC‐NL). The associations of 23 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 40 publications
3
53
0
9
Order By: Relevance
“…As for biomarkers evaluating the risk for cardiovascular events in diabetic patients, MMP3, osteopontin and N-terminal prohormone of B-type natriuretic peptide (NT-proBNP), and their combined value score are currently proposed to be introduced in evaluating diabetic patients, but first there is a need for more clear evidence that their use offers a more accurate risk stratification than the traditional risk factors [14]. …”
Section: Current Diagnostic Landmarks In Dcmmentioning
confidence: 99%
See 1 more Smart Citation
“…As for biomarkers evaluating the risk for cardiovascular events in diabetic patients, MMP3, osteopontin and N-terminal prohormone of B-type natriuretic peptide (NT-proBNP), and their combined value score are currently proposed to be introduced in evaluating diabetic patients, but first there is a need for more clear evidence that their use offers a more accurate risk stratification than the traditional risk factors [14]. …”
Section: Current Diagnostic Landmarks In Dcmmentioning
confidence: 99%
“…Various metabolic changes are comprised during long time evolving DM: the cardiac uptake of albumin-fatty acid is augmented; the storage and catabolism of endogenous triglycerides are increased, as well as the circulating lipoprotein levels, as a consequence of enhanced hepatic VLDL synthesis [14]. In DCM, calcium signaling is altered; hence the contraction-relaxation dynamic is affected, with consequent alteration of structural components and activation of various signaling pathways, including NF-kB, c-Jun N-terminal kinases, and p38 mitogen-activated protein kinases through oxidative modifications.…”
Section: Overview On Mechanisms Involved In Diabetic Heart Diseasementioning
confidence: 99%
“…In the Second Manifestations of the ARTerial disease (SMART) study, 23 novel biomarkers were evaluated for their potential to enhance predictive performance in patients with type 2 diabetes [19]. Mainly, their research was focused on other bone-related proteins (osteocalcin, osteonectin, and osteopontin), and not on OPG.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies have shown that both NT-proBNP and hs-troponin T/I could be posed predictive biomarkers in patient population with established CV disease, at higher risk of myocardial dysfunction beyond traditional CV or metabolic risk factors and DM. 5 However, the role of natriuretic peptides and cardiac troponins in subjects with pre-diabetes and also individuals with DM without established CV disease is uncertain. All these findings indicate in particular that traditional practical biomarker tools for the assessment of CV and metabolic risk in subjects with pre-diabetes, overweightobese individuals and patients with known type-1 and type-2 DM should be reappraised and novel biological markers of advanced atherosclerosis may be incorporated into risk scores.…”
mentioning
confidence: 99%